2018
DOI: 10.1093/trstmh/try056
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on renal involvement among HIV-infected patients attending a tertiary care hospital in Kolkata

Abstract: Renal involvement was less common among those on ART. Low CD4 count and body mass index (BMI) were associated with renal dysfunction. Patients on a tenofovir-based regimen had more renal involvement compared with not on a tenofovir-based regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
3
1
0
Order By: Relevance
“…The in uence of TDF to the occurrence of kidney disease is still controversial. Using univariate analysis in our study, kidney disease was found to be associated with TDF-containing regimen, which is in line with some ndings [14][15][16][17] . But a study in the USA [18] revealed that TDF-containing regimens did not lead to an increasing of the odds of kidney disease in those with low risk of chronic kidney disease (CKD).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The in uence of TDF to the occurrence of kidney disease is still controversial. Using univariate analysis in our study, kidney disease was found to be associated with TDF-containing regimen, which is in line with some ndings [14][15][16][17] . But a study in the USA [18] revealed that TDF-containing regimens did not lead to an increasing of the odds of kidney disease in those with low risk of chronic kidney disease (CKD).…”
Section: Discussionsupporting
confidence: 89%
“…The possible reasons are as follows: ART-experienced patients had lower viral load, but drugrelated kidney damage occurred in them. This can also explain why CD4 cell count is higher in patients with renal damage in our study, while prior study [9,14,19] con rmed low CD4 count was risk factor for kidney damage. Perhaps drug-related renal damage is more signi cant in Chinese population.…”
Section: Discussionsupporting
confidence: 44%
“…(2) Kidney damage might have been drug-related in ART-experienced PLWH. This can also explain why low CD4 cell count is not associated with renal damage in our study, while prior study [ 11 , 15 , 19 ] confirmed low CD4 count was a risk factor for kidney damage.…”
Section: Discussionsupporting
confidence: 41%
“…Majority of the patients on ART received TDF-containing regimen, which is one of the possible reasons why the prevalence of kidney disease among patients on ART was higher than those not on. Prior studies [ 15 18 ] confirmed that TDF was associated with kidney disease. The influence of TDF on kidney function is a well-established phenomenon with specific pathogenetic mechanisms.…”
Section: Discussionmentioning
confidence: 95%